Análise de emendas em peças de madeira para estrutura de montantes empregados em wood frame - Rodrigues, Felipe Salomão Maciel (2019)
In Brazil, civil construction is a relevant economic activity and contributes to the generation of thousands of direct and indirect jobs. However, it still uses inefficient construction techniques for making use of costly, non-renewable, polluting and difficult to reuse or recycle materials. Wood constructions, specifically in Wood Frame, can be a cost effective and environmentally friendly solution. This is because it uses renewable material and produces less waste than the conventional reinforced concrete system with masonry fences. The Wood Frame system requires the use of vertical mullions composed of seamless wood pieces. The objective was to analyze the performance of small wood pieces with top seams in the making of vertical mullions for use in wood frame structures. The use of splices aims to make Wood Frame production more economical and better ecologically suited by making use of lower value added material. Small vertical prototypes were made in small scale, with three types of top splices (female, “V” male and with side splints) and also without splices (control). Axial compression was performed in a universal mechanical testing machine, according to NBR 7190 (ABNT, 1997). The splices with lateral splints presented better results than the other splices and thus were made the Wood Frame structural panels with vertical mullions without splices (control) and with lateral splints (splices). In both cases, small-scale closure panels were used and submitted to axial compression tests. The mean maximum strength values for the seamless and side splice Wood Frame structural panels were 16.02 kN and 13.74kN, respectively, and statistically equal at 5% significance. It was concluded that it is possible to construct vertical mullions with top splints with side splints without compromising structural stability and allowing the use of smaller pieces.